ANALISIS PERCEPATAN TANAH MAKSIMUM, KECEPATAN TANAH MAKSIMUM DAN MMI DI WILAYAH SULAWESI UTARA - Massinai, Muhammad Altin; Amaliah, K. R.; Lantu, Lantu; Virman, Virman; Ismullah. M, Muhammad Fawzy (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
North Sulawesi is a region of high seismicity levels for vulnerability on the Sulawesi Island. The method for this research to detect these vulnerabilities, which examines the relationship between Peak Ground Acceleration (PGA), Peak Ground Velocity (PGV) and Modified Mercalli Intensity (MMI). The data used in this experiment is earthquake secondary recorded data. The data proceed using empirical equation that correlated with PGV and PGA - vs - earthquake intensity. The result of calculation then become basis of the data to create map of PGA and PGV also relation between PGA with PGV, with MMI and relation between PGV with MMI. The result of analysis showed that highest value PGA in North Sulawesi is 46,33gal and PGV is 20,67cm/s. The region of that have has the biggest earthquake is North Bolaang Mongondow with earthquake intensity is VII. Keywords: Earthquake, Intensity, Peak Ground Velocity, Peak Ground Acceleration.